THE PRESENTATION OF AMBIGUOUS WORDS IN THE WORKS OF ABDULLA QAHHOR (American Journal of Pedagogical and Educational Research, 2023)
The following article discusses the use of ambiguous words in Abdulla Qahhor's works, analyzing the stories of Abdulla Qahhor, where he used proverbs in the stories and how they can attract every reader.